The Effect of Using Video to Enhance Listening Ability - Maya; Sudarsono, Sudarsono; Ikhsanudin; Susilawati, Endang; Salam, Urai (Kirana Publisher (KNPub), 2023)
This research was design to examine whether videos could strengthen listening skill. It was a pre-experimental research. The participants were the Year-10 Students of Learning Group X Marketing 2 from Public Vocational High School 3 Pontianak in the Academic Year of 2022/2023. Based on the data analysis, the result showed that the video-based technique increased the student's achievement significantly in listening skill. The students showed enthusiasm during the teaching and learning process. They were very enthusiastic in applying the video technique when listening to a text. The t-test computation was higher than the t-critical value (10.36 > 2.045). The score of effect size was 1,79, and it is >1,00, categorized ‘strong’. To conclude, the video-based technique enhanced the students to listen texts better. With video, the students understood the media video helped students to understand the language even if they do not know what the words mean, by providing visual aspects of the communique. Thus, the writer suggested this technique be implemented in teaching listening ability.